Determination of nitrite in food based on its sensitizing effect on cathodic electrochemiluminescence of conductive PTH-DPP films. (15th December 2022) - Li, Yanping; Zhou, Hong; Zhang, Jihui; Cui, Bo; Fang, Yishan
Graphical abstract: Highlights: A new ECL sensing strategy for nitrite detection was proposed based on PTH-DPP film. Superior ECL efficiency occurred based on the sensitization on cathode ECL emission. High sensitivity was achieved compared to conventional cathodic ECL emitters. The sensor could be applied for nitrite determination in real samples. The ECL strategy opens up novel avenues for diversified testing in the food sector. Abstract: Herein, a novel strategy for electrochemiluminescence (ECL) detection of nitrite based on its sensitization effect on cathode ECL emission of 3, 6-di(2-thienyl)-2, 5-dihydropyrrolo [3, 4-c] pyrrole-1, 4-dione (TH-DPP) polymeric films (PTH-DPP) was formulated, by means of a one-step electropolymerization of TH-DPP with a short time on the glassy carbon electrode (GCE). It was shown that the PTH-DPP film-modified GCE exhibited a strong ECL response when S2 O8 2− was used as a co-reactant. The ECL emission could be greatly enhanced by PTH-DPP with nitrite in a K2 S2 O8 /PBS solution system and occurred at a relatively lower potential in comparison with traditional cathode ECL emitter, leading to high sensitivity and good selectivity. The ECL sensor exhibits excellent linear relationship in the ranges of 0.3 to 100 μM and 100 to 1000 μM for nitrite detection, with an outstanding detection limit of 0.08 μM (S/N = 3). The ECL sensor provides an impressive outcome for the detection of practical samples.